Stakeholder perceptions about the establishment of medical simulation-based learning at a university in a low resource setting: a qualitative study in Uganda - Najjuma, Josephine Nambi; Bajunirwe, Francis; Twine, Margaret; Namata, Tamara; Kyakwera, Catherine Kalimba; Cherop, Moses; Santorino, Data (BMC Medical Education, 2020)
Background: Simulation based learning (SBL) is a technique where teachers recreate “real life” clinical experiences for health care teams for purposes of gaining clinical skills in a safe environment. There is evidence that SBL is superior to the traditional clinical teaching methods for acquisition of clinical skills. Although it is well established in resource rich settings, there is limited experience in resource limited settings and there is uncertainty regarding how SBL will be perceived among the stakeholders in medical education. As part of the steps leading to implementation of a SBL program at a university in Uganda, we sought to describe the perceptions of various stakeholders regarding the introduction of SBL methodology into learning at a medical school in Uganda. Methods: We conducted a formative qualitative assessment using key informant interviews (KIIs) among faculty members and university administrators and focus group discussions (FGDs) among medical and nursing students at Mbarara University of Science and Technology. Data were collected till saturation point and were transcribed and analyzed manually using open and axial coding approaches to develop themes. Results: We conducted seven KIIs and three FGDs. Overall, findings were categorized into five broad themes: 1. Motivation to adopt simulation-based learning 2. Prior experience and understanding of simulation-based education 3. Outcomes arising from introduction of medical simulation 4. Drawbacks to establishment of medical simulation; and 5. Potential remedies to the drawbacks. Overall, our data show there was significant buy-in from the institution for SBL, stakeholders were optimistic about the prospects of having a new method of teaching, which they perceived as modern to complement the traditional methods. There was significant knowledge but very limited prior experience of medical simulation. Also, there was some concern regarding how students and faculty would embrace training on lifeless objects, the human resources needed and sustainability of simulation-based learning in the absence of external funding
Keywords: Medical simulation; Low and middle-income country; Simulation center; Stakeholders